HLA‐A*24:02 is associated with metronidazole‐induced cutaneous adverse drug reactions in Han Chinese individuals: A pilot case‐control study with both HLA gene and T cell receptor repertoire analysis. Issue 2 (4th September 2019) - Yang, Fanping; Jiang, Menglin; Zhang, Wen; Qiao, Yimeng; Chen, Sheng‐an; Wang, Dan; Zhu, Huizhong; Zhang, Jin; Qin, Shengying; Zhu, Qinyuan; Lv, Youbiao; Xing, Qinghe; et al.
Abstract: Metronidazole, a widely used drug for the treatment of infections with anaerobic and facultative anaerobic bacteria and protozoa, can frequently cause metronidazole‐induced cutaneous adverse reactions (McADRs). The aim of the present study was to investigate the association between human leucocyte antigen (HLA) alleles and McADRs in a Chinese Han population. The frequency of HLA‐B*24:02 carriers among the McADR patients was 73.3%, which was significantly higher than that of the population controls (32.16%, OR = 5.80, 95% CI = [1.80‐18.72], P c = 0.004) and of the metronidazole‐tolerant patients (26.67%, OR = 7.56, 95% CI = [2.02‐28.35], P c = 0.004). Molecular docking showed that metronidazole and one of its major metabolites had the potential to bind in the HLA groove and that there was a relatively stable binding state of the HLA‐B*24:02‐metronidazole/the metabolite complex. The CDR3 repertoires of both T cell receptor (TCR)Vα and Vβ of the patients showed a significantly skewed or an oligoclonal distribution. The TCRVβ CDR3 of the patients shared a similar motif, "CASSxxxxxxQxF." The current study demonstrated that both the HLA‐A*24:02 allele and TCR are involved in the pathogenesis of McADRs.